Effect of postharvest UV-C treatment on the bacterial diversity of Ataulfo mangoes by PCR-DGGE, survival of E. coli and antimicrobial activity - Fernández-Suárez, Rocio; Ramírez-Villatoro, Guadallupe; Díaz-Ruiz, Gloria; Eslava, Carlos; Calderón, Montserrat; Navarro-Ocaña, Arturo; Trejo-Márquez, Andrea; Wacher, Carmen (Frontiers in Microbiology, 2013)
Since Mexico is the second largest exporter of mangoes, its safety assurance is essential. Research in microbial ecology and knowledge of complex interactions among microbes must be better understood to achieve maximal control of pathogens. Therefore, we investigated the effect of UV-C treatments on bacterial diversity of the Ataulfo mangoes surface using PCR-DGGE analysis of variable region V3 of 16S rRNA genes, and the survival of E. coli, by plate counting. The UV-C irradiation reduced the microbial load on the surface of mangoes immediately after treatment and the structure of bacterial communities was modified during storage. We identified the key members of the bacterial communities on the surface of fruits, predominating Enterobacter genus. Genera as Lactococcus and Pantoea were only detected on the surface of non-treated (control) mangoes. This could indicate that these genera were affected by the UV-C treatment. On the other hand, the treatment did not have a significant effect on survival of E. coli. However, genera that have been recognized as antagonists against foodborne pathogens, were identified in the bands patterns. Also, phenolic compounds were determined by HPLC and antimicrobial activity was assayed according to the agar diffusion method. The main phenolic compounds were chlorogenic, gallic and caffeic acids. Mango peel methanol extracts (UV-C treated and control mangoes) showed antimicrobial activity against strains previously isolated from mango, detecting significant differences (P<0.05) among treated and control mangoes after 4 and 12 days of storage. Ps. fluorescens and Ps. stutszeri were the most sensitive.